PERANAN PEMIMPIN OPERATION HEAD TERHADAP KINERJA PEGAWAI PT. PERTAMINA (PERSERO) SAMARINDA - ., Abdikassalam (PREDIKSI, 2015)
Abdikassalam, Operation Leader Role Head Performance Against Workers of PT. Pertamina (Persero) Samarinda under the guidance of Mr Drs. Damai Darmadi, M.Si and Mr H. Drs. Achmad Jubaidi, M.Si.This study aims to determine to determine the role of leader of Performance Against Workers of PT. Pertamina (Persero) Samarinda.This type of research used in this research is the study of associative or relationships, is a research that aims to determine the relationship between two or more variables.The results showed that of the data analysis and hypothesis testing in mind that the resulting product moment coefficient was r = 0.494. Based on the results of the data analysis, it is clear that the role of leader of the variables had a significant relationship with performance variables Workers.Thus it can be said that the goal of this research can be achieved with good, problems can be solved and data analysis can be proved.